The Digital Technology in Supporting Nursing Services During The Covid-19 Pandemic: A Literature Review - Saktiningtiyas, Devi Ruchama’; Asmaningrum, Nurfika; Nur, Kholid Rosyidi Muhammad (jitek, 2022)
Digital technology plays an important role in helping health workers and improving health services. During the COVID-19 pandemic, digital technology can be an apt solution in supporting nursing/health services to patients. This study aimed to explain digital technology in terms of its forms, functions, and obstacles when harnessed to support nursing/health services during the COVID-19 pandemic. The research databases were established by sourcing articles from Pubmed, ProQuest, Springer Link, Sage Journals, and Google Scholar, focusing on articles published in 2019-2022. The research results found 5 articles discussing the forms and functions of digital technology, 2 articles discussing the functions and barriers of implementing digital technology, and 4 articles discussing the forms, functions, and barriers of implementing digital technology. Most of the forms of digital technology implementation to support nursing/health services during the COVID-19 pandemic involve virtual visits, online consultations, and monitoring patient conditions remotely. The use of digital technology in supporting nursing/health services during the COVID-19 pandemic affords various gains for health workers, patients, and patient families, which serve as the drive to improve services. In addition, these obstacles can serve as the cornerstones in evaluating the use of digital technology for future improvement. Future studies are suggested to examine one form of digital technology for nursing/health services that already exist.